Psychoanalysis, cinema and subjectivity: how seventh art interfers in the construction and reconstruction of subjectivit (Research, Society and Development, 2019)
The objective of this study was to verify the influence of the American series Friends in the viewer subjects, analyzing the emotional reactions that it can mobilize in the individual and their contributions in the process of construction and reconstruction of the subjectivity through the conceptions of Psychoanalysis. The methodology used to evaluate the episodes was the film analysis. Through the analyzes and interpretations of the series it can be observed that both the episodes that mobilize positive emotions and those that manifest negative reactions tend to generate important reflections in the viewer (a) that may have important repercussions on the subjectivity of the subject. It is concluded that the cinema especially the series analyzed, can mobilize emotional reactions and broaden the field of subjective experience of the spectator, important factors that may contribute in the processes of subjectivation of the individual.